Nanocellulose-based composites for 3D printed stimuli-responsive swelling hydrogel - Mohd Shaiful Sajab; Denesh Mohan; Teo Tzyy Ling; Hatika Kaco; Wan Hafizi Wan Ishak; Gongtao Ding (Elsevier, 2024)
Indexed by WOS/Scopus/ERA